Tunneling the barriers of blockchain technology in remanufacturing for achieving sustainable development goals: A circular manufacturing perspective. (31st March 2022) - Govindan, Kannan
Abstract: As a concern with manufacturing industries, circular economy (CE) practices—often labeled "circular manufacturing (CM)"—are industrial tasks through which several circular economy principles have been integrated. Among these circular manufacturing strategies, "3R" (recycle, refurbish/remanufacture, and reuse/redistribute) is the key strategy that assists the manufacturing industry with closing the loop for sustainability. An effective inclusion and management of 3R lead a firm to a greater likelihood of successfully integrating CE and CM. In recent years, remanufacturing has gained greater prominence, especially with the emergence of technology, including cyber‐physical systems. These technologies assist the remanufacturing firm with efficient take‐back systems through tracking. However, data transferred through these technologies among value chain partners in remanufacturing are not reliable. Due to the lack of trust and transparency, value chain partners are hesitant to participate in remanufacturing supply chains. To address the limitation of technologies in remanufacturing, blockchain has been introduced to secure the data. Despite the advantages of blockchain technology, practitioners face difficulties in integrating these blockchain technologies into the remanufacturing context. Several earlier studies addressed the challenges of implementing blockchain, but no earlier studies have specifically examined remanufacturing industries, which are entirely different from forward supply chain industries. Concerning the fact, this study identifies the barriers that exist with the implementation of blockchain technology in the application of the remanufacturing sector. A framework has been proposed and validated in a Danish automotive parts remanufacturing company. Multi‐criteria decision‐making method has been used to identify the effective and most influential barriers among common barriers. Results reveal that "scaling of technology" (B6 ) is the key barrier of BCT implementation in remanufacturing context. This study concludes with useful discussions based on the results along with the recommendations to eradicate those influential barriers and their respective impacts on SDGs (SDG4, SDG8, SDG9, and SDG17). Finally, this study sheds light on future enhancements on the integration of blockchain technology in remanufacturing to reap several benefits of circular manufacturing.